DCNC: throughput maximization via delay controlled network coding for wireless mesh networks. Issue 2 (4th August 2014) - Qu, Yuben; Dong, Chao; Chen, Chen; Wang, Hai; Tian, Chang; Tang, Shaojie
Abstract: Network coding (NC) can greatly improve the performance of wireless mesh networks (WMNs) in terms of throughput and reliability, and so on. However, NC generally performs a batch‐based transmission scheme, the main drawback of this scheme is the inevitable increase in average packet delay, that is, a large batch size may achieve higher throughput but also induce larger average packet delay. In this work, we put our focus on the tradeoff between the average throughput and packet delay; in particular, our ultimate goal is to maximize the throughput for real‐time traffic under the premise of diversified and time‐varying delay requirements. To tackle this problem, we propose DCNC, a delay controlled network coding protocol, which can improve the throughput for real‐time traffic by dynamically controlling the delay in WMNs. To define an appropriate control foundation, we first build up a delay prediction model to capture the relationship between the average packet delay and the encoding batch size. Then, we design a novel freedom‐based feedback scheme to efficiently reflect the reception of receivers in a reliable way. Based on the predicted delay and current reception status, DCNC utilizes the continuous encoding batch size adjustment to control delay and further improve the throughput. Extensive simulations show that, when faced with the diversified and time‐varying delay requirements, DCNC can constantly fulfill the delay requirements, for example, achieving over 95% efficient packet delivery ratio (EPDR) in all instances under good channel quality, and also obtains higher throughput than the state‐of‐art protocol. Copyright © 2014 John Wiley & Sons, Ltd. Abstract : We propose Delay Controlled Network Coding protocol (DCNC), which can improve the throughput for real‐time traffic by dynamically controlling the delay in WMNs. Extensive simulations show that, when faced with the diversified and the time‐varying delay requirements, DCNC can constantly fulfill the delay requirements, for example, achieving over 95% efficient packet delivery ratio in all instances under good channel quality, and also obtains higher throughput than the state‐of‐the‐art protocol.